Macroeconomic Models for the PC+L862 - Bier, Willem (IMF Working Papers; Working Paper ;, 1992)
This paper describes a computer program with which one can build macroeconomic models. It is possible to specify up to eighteen behavioral equations, each with between five and eleven independent variables. For certain variables, the user can decide whether they will be endogenous or exogenous. Many policy simulations dealing with adjustment and growth issues can be performed with this program by varying any of the exogenous variables, and these experiments can be repeated for different model specifications. This paper describes a number of experiments with a model of an open economy where output and prices are endogenous.